Sosialisasi Penanganan Luka Ringan yang Tepat pada Remaja di SMP Negeri 1 Kairatu - Jusuf Leiwakabessy; Delsi Pattinasarany; Vallery Kustianti Marriot Masbait; Ibnu Salman Hasan; Sanfia Fella Masahe; Zhamira Azzahra Tuankotta; Laura Bianca Sylvia Huwae (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
Minor wounds, such as abrasions, scratches, or small cuts, are commonly experienced by teenagers, especially in school environments. However, improper treatment of minor wounds can lead to infections and more severe complications. This study aims to raise awareness and educate students at SMP Negeri 1 Kairatu on the proper management of minor wounds. The research employs a descriptive approach with an interactive educational method involving presentations, discussions, and live demonstrations. Respondents in this study were students from grades 7 to 9. The results indicated that prior to the socialization, most students had inadequate knowledge regarding proper wound care, often resorting to inappropriate methods (e.g., using toothpaste or oil). After the educational intervention, there was an 85% increase in students’ understanding of proper wound management, such as cleaning wounds with clean water, applying antiseptics, and covering wounds with sterile bandages. The socialization program also successfully raised awareness among students about the importance of wound hygiene to prevent infections. Thus, this initiative proved effective in enhancing teenagers' knowledge of proper wound care practices.